2004
DOI: 10.1111/j.1365-2249.2004.02351.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial heat shock protein 70 induces interleukin-10 production: immunomodulation of synovial cell cytokine profile and dendritic cell maturation

Abstract: SUMMARYCytokines are key modulators of the immune responses that take place in the inflamed synovium of arthritis patients. Consequently, substances that can reverse the inflammatory profile of the inflamed joint are potential tools for clinical management of the disease. Mycobacterial heat shock protein 70 (MTBHSP70) has been found to protect rats from experimentally induced arthritis through the induction of interleukin (IL)-10-producing T cells. In this study, we have demonstrated that MTBHSP70 induces IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 38 publications
2
49
0
1
Order By: Relevance
“…Overexpression or induction of intracellular Hsp70 (by stress or by Hsp70-inducing compounds) has been shown to decrease nuclear NFkB translocation, inducible nitric oxide synthase expression, and production of TNF-a, IL-6, IL-1b, and NO Dokladny et al, 2010;Kim et al, 2012;Muralidharan et al, 2014). Accordingly, it has been demonstrated that extracellular Hsp70 diminishes LPS-induced TNF-a by bone marrow-derived dendritic cells in vitro and induces IL-10 production by synovial cells from patients with arthritis (Detanico et al, 2004). The anti-inflammatory cytokine IL-10 suppresses LPS-induced macrophage activation by inhibiting the expression of specific TLR-induced proinflammatory genes referred to as "IL-10 counter-regulated genes" (Moore et al, 1993;Cardwall and Weaver, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression or induction of intracellular Hsp70 (by stress or by Hsp70-inducing compounds) has been shown to decrease nuclear NFkB translocation, inducible nitric oxide synthase expression, and production of TNF-a, IL-6, IL-1b, and NO Dokladny et al, 2010;Kim et al, 2012;Muralidharan et al, 2014). Accordingly, it has been demonstrated that extracellular Hsp70 diminishes LPS-induced TNF-a by bone marrow-derived dendritic cells in vitro and induces IL-10 production by synovial cells from patients with arthritis (Detanico et al, 2004). The anti-inflammatory cytokine IL-10 suppresses LPS-induced macrophage activation by inhibiting the expression of specific TLR-induced proinflammatory genes referred to as "IL-10 counter-regulated genes" (Moore et al, 1993;Cardwall and Weaver, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory cytokine, IL-10, has been shown to be cytoprotective in macrophages (51) and induced by the addition of exogenous HSP70 in synovial cells (52,53), suggesting that HSPs play an active role in suppressing inflammation by the regulation of IL-10. Here we provide evidence that secretion of IL-10 may be regulated by HSP70BЈ.…”
Section: Discussionmentioning
confidence: 99%
“…However, the in vivo studies also showed a mild early IFN-g expression, which is in disagreement with our in vitro results that showed high p40 IL-12/Il-23 and IL-18 expression. Thus, other unknown factors could be contributing to prevent [17] and/or some mycobacterial components might also modify it, being expressed during this phase of infection [18,19]. One possibility whereby Mtb strains might modulate differential expression of cytokines and iNOS in BMDM could be through bacterial components interacting with macrophage receptors.…”
Section: Discussionmentioning
confidence: 99%